Updated ACVIM consensus statement on leptospirosis in dogs - Jane E. Sykes; Thierry Francey; Simone Schuller; Robyn A. Stoddard; Larry D Cowgill; George E. Moore (Journal of Veterinary Internal Medicine, 2023)
Abstract Since publication of the last consensus statement on leptospirosis in dogs, there has been revision of leptospiral taxonomy and advancements in typing methods, widespread use of new diagnostic tests and vaccines, and improved understanding of the epidemiology and pathophysiology of the disease. Leptospirosis continues to be prevalent in dogs, including in small breed dogs from urban areas, puppies as young as 11 weeks of age, geriatric dogs, dogs in rural areas, and dogs that have been inadequately vaccinated for leptospirosis (including dogs vaccinated with 2‐serovar Leptospira vaccines in some regions). In 2021, the American College of Veterinary Internal Medicine (ACVIM) Board of Regents voted to approve the topic for a revised Consensus Statement. After identification of core panelists, a multidisciplinary group of 6 experts from the fields of veterinary medicine, human medicine, and public health was assembled to vote on the recommendations using the Delphi method. A draft was presented at the 2023 ACVIM Forum, and a written draft posted on the ACVIM website for comment by the membership before submission to the editors of the Journal of Veterinary Internal Medicine. This revised document provides guidance for veterinary practitioners on disease in dogs as well as cats. The level of agreement among the 12 voting members (including core panelists) is provided in association with each recommendation. A denominator lower than 12 reflects abstention of ≥1 panelists either because they considered the recommendation to be outside their scope of expertise or because there was a perceived conflict of interest.